The Influence of Grammar and Vocabulary Mastery on Students’ Reading Comprehension at Language Development Center of UIN SUSKA RIAU - Muharni Muharni (J-SHMIC: Journal of English for Academic, 2017)
The aims of the research were to find out the influences among the variables; (1) to find out the influence of grammar mastery on the students’ reading comprehension, (2) to find out the influence of vocabulary mastery on the students’ reading comprehension, and (3)to find out the influence of grammar (X1) and vocabulary mastery on the students’ reading comprehension. The design of this research was a corelational research. The population was 150 the second level students of Language Development Center of UIN SUSKA Riau and 90 students were taken clusterly as samples. In collecting data, multiple choice tests were used as intruments. In the result of analysing data,Pearson Product Moment Correlation (SPSS 20) was used. The first finding of the research indicated that there was a positive influence between X1 and Y variables which was proved by two ways in interpreting the result of correlation where the value rxy=0.811 was between 0.800 – 1.00 meant very high influence and by comparing the value of rxy =0.811 with ttable was 0.205<0.811>0.267 that meant the rxy was a higher influence than ttable. The second finding, there was a positive influence between X2 and Y variables which was showed by two ways in interpreting the result of correlation where the value rxy=0.735 was between 0.600 – 0.800, that meant high influence and by comparing the value of rxy with ttable  was 0.205<0.735>0.267 that meant rxy was higher than ttable. The last finding, there was a positive influence between X1, X2 and Y variables altogether which was proved by two ways in interpreting the result of correlation where the value was between 0.800 – 1.00, that meant very high influence and by comparing the value of with ttable was “0.205<0.82969>0.267” that meant was higher than ttable.